Effect of relationship commitment on the underlying motivations to forgive - Tang, Yan Yue (2014)
Warm romantic relationships are crucial for personal well-being and this highlights the need to study relationship persistence behavior such as forgiveness. This study extends existing research on the link between relationship commitment and likelihood to forgive, by examining the differential effects of relationship commitment on the three motivations that underlie forgiveness – revenge, avoidance, and benevolence. In addition, this study addresses the moderating role of implicit need of affiliation on the relationship between commitment and likelihood to forgive, as well as between commitment and the underlying motivations to forgive. Priming procedures were used to manipulate participants’ relationship commitment, before accessing their motivational changes and likelihood to forgive after a relationship transgression. As highly committed individuals have stronger desire to maintain and restore their relationship, they were expected to be more likely to forgive than lowly committed individuals. Additionally, they were expected to have lower revenge, lower avoidance, and higher benevolence motivations towards the transgressing partner. Transgression severity and experience were controlled in analyses and as expected, highly committed participants had significantly lower revenge motivations than lowly committed individuals. However, implicit need for affiliation did not moderate the relationship, perhaps because it is a more distal predictor of forgiveness than relationship commitment. Relationship commitment is capable of reducing revenge motivations that are detrimental to the well-being of a relationship, and this suggests the importance of commitment in the restoration of damaged relationship and its potential in couples therapy.